2020
DOI: 10.1038/s41598-020-77365-8
|View full text |Cite
|
Sign up to set email alerts
|

Detection of degenerate Stokes index states

Abstract: Stokes phase is the phase difference between orthogonal component states in the decomposition of any polarization state. Phase singularities in the Stokes phase distribution are Stokes singularities of an inhomogeneous polarization distribution. Under circular decomposition, Stokes phase distribution $$(\phi _{12})$$ ( ϕ 12 ) represents polarization azimuth $$(\gamma )$$ ( γ ) distribution and the singularities present in it are polarization singularities. Therefore, the charge of the Stokes vortices d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(6 citation statements)
references
References 60 publications
(72 reference statements)
0
6
0
Order By: Relevance
“…Nevertheless, to identify the OAMs with diffraction patterns, the propagation of has to be involved 5 . According to our previous report 31 , we have applied adjustable combination gratings ( and in Fig.…”
Section: Theory and Methodologymentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, to identify the OAMs with diffraction patterns, the propagation of has to be involved 5 . According to our previous report 31 , we have applied adjustable combination gratings ( and in Fig.…”
Section: Theory and Methodologymentioning
confidence: 99%
“…Characteristics of circularly polarized vortex beams were examined by adopting the decomposition of cylindrical bases 3 and a special polarization grating 4 . Degenerate Stokes states were differentiated by a method associated with transformations of diffraction and polarization 5 . Additionally, studies on OAM light beams have shown promising applications in various fields.…”
Section: Introductionmentioning
confidence: 99%
“…Polarization conversions between linear and circular, and the manipulation of optical angular momentum in structured light fields are essential topics in optical field manipulation, with significant fundamental research interest and practical applications. The spin angular momentum (SAM) relies on circular polarization [27][28][29] (referred to as the S 3 in Figure 4), while the OAM is related to the gradient phase distribution [30]. The SAM and OAM densities of structured beams in the focal region can be calculated as follows:…”
Section: Effect Of a High-order Twisting Phase On The Optical Angular...mentioning
confidence: 99%
“…Due to their unique propagation properties spin-orbit beams have found numerous applications in high-resolution imaging, communication protocols, and optical metrology 27 29 and a wealth of characterization techniques based on Stokes polarimetry have been developed 30 32 . Ref.…”
Section: Introductionmentioning
confidence: 99%